The Place And Classification Of Agroturism In Tourism Types (Texas Journal of Engineering and Technology, 2024)
This article discusses the specific role of agrotourism in the tourism system and its classification, one of the new and currently developing types of tourism. It is emphasized that one of the main goals of agrotourism is to organize the broad use of the tourist potential of rural areas in the sustainable development of their areas.